The development of a wide range CRISPR-Cas9 gene editing system - Bisschoff, Eduvan (University of the Free State, 2019)
CRISPR is a revolutionary method to effectively and efficiently alter the genomic make-up of an organism. Unlike any other genetic engineering tool or technique, CRISPR is remarkably cheaper, simpler and faster to perform. In biotechnology, the best eukaryotic organism for research is yeast, due to their fast growth rate and ease of manipulation compared to multicellular organisms. Hence the aim of the study was the development of a wide range CRISPR-Cas9 system for a wide variety of different yeasts for easy and fast gene editing. The system were validated in Saccharomyces cerevisiae and six other non-conventional yeast. System construction began with the incorporation (separately) of three different optimized CAS9 (optimized for expression in Pichia pastoris, Candida albicans and Homo sapiens) genes into the wide range pKM180 vector. The three different CAS9 construct were then tested for correct expression of the Cas9 protein and the effects thereof in all the yeasts. Through western blot analysis it was observed that all three of the different Cas9 proteins were expressed successfully in the different yeasts. However, all of the Cas9 proteins had a negative effect on the growth of the yeast. For the completion of the CRISPR-Cas9 system, a Ribozyme‐gRNA‐Ribozyme cassette was incorporated into the wide range CAS9 vector, containing the C. albicans optimized CAS9. The system was then validated with successful disruption of the ADE2 gene in all of the yeasts. This proved that the wide range CRISPR-Cas9 system was applicable in a wide variety of different yeasts, thus allowing for rapid, cost-effective genetic manipulation of biotechnologically relevant yeast strains.
Dissertation (M.Sc. (Microbiology))--University of the Free State, 2019
Keywords: Arxula adeninivorans; Debaryomyces hansenii; Kluyveromyces lactis; Ogataea polymorpha; Komagataella phaffii; Saccharomyces cerevisiae; Yarrowia lipolytica; Pichia pastoris; Candida albicans optimized CAS9; CRISPR-Cas9; Wide range CRISPR-Cas9 system